2003
DOI: 10.1038/sj.bjc.6601040
|View full text |Cite
|
Sign up to set email alerts
|

PAX7 expression in embryonal rhabdomyosarcoma suggests an origin in muscle satellite cells

Abstract: Rhabdomyosarcoma (RMS) is a common paediatric soft tissue sarcoma that resembles developing foetal skeletal muscle. Tumours of the alveolar subtype frequently harbour one of two characteristic translocations that juxtapose PAX3 or PAX7, and the forkheadrelated gene FKHR (FOXO1A). The embryonal subtype of RMS is not generally associated with these fusion genes. Here, we have quantified the relative levels of chimaeric and wild-type PAX transcripts in various subtypes of RMS (n ¼ 34) in order to assess the relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
71
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 30 publications
7
71
0
5
Order By: Relevance
“…In contrast, Sca1 + cells, a population of bipotent fibrogenic/adipogenic precursors that lack myogenic activity but reside in skeletal muscle, induce sarcomas that lack myogenic differentiation features in most tumors. These findings support the origination of RMS in cells of the myogenic lineage (3,7,8,46) and demonstrate that the preexisting lineage commitment of the target cell into which oncogenetic hits are introduced is critical in determining the phenotypic properties of sarcomas in muscle (3,7,8,46). Similar studies performed in the hematopoietic system (47) suggest that the influence of cellular context on the outcome of oncogenesis is likely to be a conserved feature of both liquid and solid malignancies of mesodermal lineage, perhaps reflecting inherent differences in established epigenetic marks within distinct cancer cells-of-origin.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, Sca1 + cells, a population of bipotent fibrogenic/adipogenic precursors that lack myogenic activity but reside in skeletal muscle, induce sarcomas that lack myogenic differentiation features in most tumors. These findings support the origination of RMS in cells of the myogenic lineage (3,7,8,46) and demonstrate that the preexisting lineage commitment of the target cell into which oncogenetic hits are introduced is critical in determining the phenotypic properties of sarcomas in muscle (3,7,8,46). Similar studies performed in the hematopoietic system (47) suggest that the influence of cellular context on the outcome of oncogenesis is likely to be a conserved feature of both liquid and solid malignancies of mesodermal lineage, perhaps reflecting inherent differences in established epigenetic marks within distinct cancer cells-of-origin.…”
Section: Discussionsupporting
confidence: 74%
“…STS vary clinically and histopathologically (1,2), and this heterogeneity may result from differences in the lineage commitment and differentiation state of the sarcoma cell-of-origin, from genetic or epigenetic changes that occur during transformation, or from a combination of these factors (3). Sarcomas with myogenic features constitute the large and varied category of rhabdomyosarcomas (RMS) (4,5), for which satellite cells (6,7), more differentiated muscle-lineage cells (3,8), and undifferentiated mesenchymal cells (9) have been discussed as putative cells-of-origin. Still, the network of cellular and molecular events driving sarcomas in muscle is largely unknown (10).…”
mentioning
confidence: 99%
“…Human primitive skeletal muscle cell precursors infected with retroviruses encoding T/t-Ag, hTERT and H-rasG12V gave rise to highly heterogeneous tumors occasionally displaying features of the RMS, whereas human skeletal muscle myoblasts form embryonal RMSs (Linardic et al, 2005). PAX7 expression in the latter suggests an origin from muscle satellite cells (Tiffin et al, 2003), situated beneath the basal lamina, that surround each myofiber and function as myogenic precursors for muscle growth and repair. Transplantation of single intact myofibers into radiation-ablated muscles has demonstrated that satellite cells are self-sufficient as a source of regeneration (Collins (Sharp et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to determine whether active Hh signaling occurs in a less differentiated subset of cells within primary rhabdomyosarcoma tissue. Whether rhabdomyosarcoma arises secondary to aberrant satellite cell programming is also a subject of ongoing investigation (Keller et al, 2004a, b;Tiffin et al, 2003). Figure 4 Multiple domains of Gli1 are required to inhibit transcriptional activation by MyoD.…”
Section: Discussionmentioning
confidence: 99%